Modernidad, estética y subjetividad. Una reconstrucción histórico-conceptual de las reapropiaciones del pensamiento de Friedrich Schlegel en el marco de la filosofía alemana contemporánea - Galfione, Verónica (2018)
“Modernity, Aesthetics and Subjectivity. A Historical-conceptual Reconstruction of the Reappropriations of Friedrich Schlegel’s Thought Within the Framework of Contemporary German Philosophy”. In this paper we analyze the interpretation of Friedrich Schlegel’s romantic thought developed by K. H. Bohrer and M. Frank. The aim is to show how, through this historical reference, the aforementioned authors reconstruct a conception of subjectivity that breaks with the modern postulate of an instituting subject and that allows to overcome the poststructuralist thesis of the death of the subject. However, neither this alternative conception of the subject, nor the way in which the aesthetic dimension is characterized by Bohrer and Frank, are free of difficulties. As we will see towards the end of this paper, their anti-idealistic reading of Schlegel’s work is not only strongly unilateral, but unable to realize the specificity of contemporary artistic production.